Promoting secondary school learners' curiosity towards science through digital public displays - Otero, Nuno (2013)
This paper contributes to the understanding of how digital public displays can be utilized in schools taking into consideration educational goals. This work is part of a currently on-going research project that aims to promote students' curiosity in science and technology through creative film-making, collaborative editing activities, and content sharing. In order to explore the design space concerning digital public displays for schools' contexts, six workshops with secondary school teachers in two different countries were conducted to elicit sensitivities towards possible features and interaction techniques as well as inquire about expectations and technology adoption. Our findings suggest that teachers are receptive to the technology and were able to generate scenarios that take advantage of the possibilities offered by digital public displays to stimulate learning processes.However, there are several crucial elements regarding management and control of content that need to be carefully crafted/designed in order to accommodate each schools' organizational issues.